Deconstruyendo conceptos: Las guerras de venganza y las relaciones internacionales - Tchinhama, Laurindo Paulo Ribeiro (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2021)
The book 'As guerras de vingança e as Relações Internacionais: um diálogo com a Antropologia Política sobre os Tupi-Guarani e o Yanomami’ [Revenge wars and International Relations: a dialogue with Political Anthropology about the Tupi-Guarani and the Yanomami] was originally published in Brazil in 2019 in Portuguese. It contains eight chapters in which Alberto Montoya Correa Palacios Jr. suggests a critical reflection about the predominant concepts in International Relations (IR) literature. Through an interdisciplinary path, the author searches in Political Anthropology, Ethnography and Sociology to highlight  Brazilian national literature to analyze the wars of  Tupi-Guarani and Yanomami indigenous peoples, relating them to the IR field in an intent to fill the existing conceptual gaps through interpretations and analytical features about war and revenge, deconstructing Eurocentric visions vague of solid arguments about savagery, cannibalism, revenge war and in Amerindian indigenous societies. The author's central argument is to purpose and test the concept of revenge war as an analytical tool for IR.